Imaging diagnosis of pancreatic cancer and preoperative imaging evaluation of resectability and staging - CHEN Lu (Linchuang Gandanbing Zazhi, 2016)
Pancreatic cancer is an invasive malignant tumor with a high mortality rate. As the preferred imaging method for pancreatic imaging, multi-slice CT angiography can evaluate the presence or absence, extent, and degree of invasion of peripancreatic major vessels to provide reliable evidence for tumor staging and surgical resectability evaluation. As an important supplementary method of CT, magnetic resonance imaging has an important guiding value in disease diagnosis, liver metastasis, and prognostic evaluation. Vascular invasion of pancreatic cancer is the main indicator for preoperative evaluation of respectability. Lymph node metastasis, distant metastasis, neural invasion of pancreatic cancer, and hepatic artery abnormalities are influencing factors for patients′ prognosis. It is pointed out that preoperative imaging evaluation for patients with pancreatic cancer has guiding significance for the development of treatment regimens, selection of surgical procedures, and prognostic evaluation.